Sistem Lapor Dini Bencana Kebakaran Berbasis Mobile di Kota Bitung - Abdul Fajar Duke; Made Krisnanda; Quido C. Kainde (Program Studi Teknik Informatika, 2020)
Abstract—Fire is one of the disasters that comes difficult to predict, aside from being unwanted by the community, it is also often difficult to control if the fire already becomes large. As for the obstacles that often occur, firefighters are late getting fire reports and also difficulty in finding the location of fires due to lack of information. system development is done by the writer in this study using the Waterfall model (Presmann, 2010). system modeling is documented using DFD (Data Flow Diagrams). The results of this study are a mobile-based early fire disaster detection system with several features to overcome community problems in reporting a fire disaster and help firefighters to get an accurate location and the fastest route to the fire location.